2013
DOI: 10.1118/1.4773883
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo approach to validation of FFF VMAT treatment plans for the TrueBeam linac

Abstract: The authors have presented a method for making the Varian IAEA compliant 6 MV FFF phase space file of the TrueBeam linac compatible with BEAMnrc/DOSXYZnrc. After benchmarking the modified phase space against measurement, they have demonstrated its potential for use in MC based quality assurance of complex delivery techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 26 publications
5
48
3
Order By: Relevance
“…This pattern persists when we calculate output factors at dmax and is also reported by other authors for the TrueBeam 1 , 2 , 4 and Varian 21EX (16) . Our measured output factors agree better than 1% with those reported by Gete et al, (7) except for the 1×1 field which is 1% different from their Monte Carlo calculation.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This pattern persists when we calculate output factors at dmax and is also reported by other authors for the TrueBeam 1 , 2 , 4 and Varian 21EX (16) . Our measured output factors agree better than 1% with those reported by Gete et al, (7) except for the 1×1 field which is 1% different from their Monte Carlo calculation.…”
Section: Resultssupporting
confidence: 89%
“…Removing the filter results in a highly forward‐peaked beam profile, increases the dose rate, and softens the beam. While several recent papers have summarized the dosimetric characteristics of these beams 1 , 2 , 3 and others have reported commissioning results of the anisotropic analytical algorithm (4) or Monte Carlo, 5 , 6 , 7 scarce data exist on modeling these beams with the collapsed cone convolution superposition (CCCS) algorithm as implemented in the widely used Pinnacle 3 treatment planning system (Philips Radiation Oncology Systems, Fitchburg, WI). Stathakis et al (8) reported their experience commissioning the CCCS algorithm for 6 and 18 MV unflattened beams by overriding interlocks related to the flattening filter, but no patients were treated with this configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Although this approach may provide more uniform results across the research community, the limitation of a defined number of original particles may result in simulation bias if not validated. Previous studies have validated the accuracy of version‐1 of the Varian phase‐space files with measurement data 15 , 16 . The version‐1 phase‐space files are stored in a cylindrical space.…”
Section: Introductionmentioning
confidence: 99%
“…Properties of the FFF beams for these machines, usually determined during the commissioning process, have been subsequently reported 4 , 5 , 6 . Comparisons between Monte Carlo calculations and experimental measurements have been performed to confirm that simulations accurately model accelerator geometry 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 95%